Comparative Study of the Teachings in Adabul ‘Ālim wal Muta’allim and the Actual Character Formation of Students at Dormitory H, Pondok Pesantren Ngalah - Tsaniyah, Ma'rifatus; Mubarok, Achmat (Literacy: Journal of Education and Social Science, 2025)
This study explores the concept of seeking knowledge in the classical Islamic text Adabul ‘Ālim wal Muta’allim by KH. Hasyim Asy’ari and its relevance to the personality development of students (santri) at Dormitory H of the Ngalah Islamic Boarding School. The book emphasizes core values such as sincerity, humility, diligence, patience, and respect for teachers and knowledge, which serve as the foundation for character formation in Islamic education. This research uses a qualitative approach, employing literature review, observation, and interviews with caretakers and students. The focus includes understanding the contents of the book, the personality profile of the students, and the relationship between the two. Findings indicate that the values taught in the book remain highly relevant and are reflected in the students’ behavior, such as discipline, sincerity, and modesty. However, challenges such as the influence of technology and the lack of integration of the book’s values in non-formal activities still need to be addressed. The study concludes that Adabul ‘Ālim wal Muta’allim is not merely a classical text but also a practical guide for shaping knowledgeable and virtuous students, offering a solution to the current crisis of student character.